treet Harassment as Predictor of Self-Esteem Levels on Women Victims in Emerging Adulthood - Dwi Arini Putri, Kirana; Herdiana, Ike (Rifa'Institute, 2023)
Introduction: Street harassment phenomenon such as cat-calling, breast-grabbing, and stalking are increasingly occurring in Indonesia. The increasingly widespread phenomenon of street harassment creates a unsecure and discomfort for the community and causes a decrease in level of self-esteem for the victims. Objective: This study aims to determine the effect of experience of street harassment on the level of self-esteem in Indonesian women in the emerging adulhood group. Method: This study uses a quantitative approach with survey data collection. The participants of this study is 100 female aged 18-25 years old. The measuring instruments used were the 8 item Street Harassment Scale (SHS) that had been modified and the 10 item Rosenberg's Self-Esteem Scale (RSES) designed. Data analysis used in this research is simple regression analysis and performed by Jamovi 2.3.21. Result and Discussion: As much as 60% of the level of self-esteem in victims of street harassment can be explained by the experience of street harassment (R Square = 0,605). Conclusions: From the results of research data analysis, it is known that there is a role of experience of street harassment on the level of self-esteem in women in the young adult age group